Hodnocení finanční situace podniku a návrhy na její zlepšení - Jarcovják, Jindřich (Vysoké učení technické v Brně. Fakulta podnikatelská, 2024)
Bakalářská práce se zabývá zhodnocením finanční situace společnosti Podhoran Lukov, a.s. Finanční analýza byla provedena v letech 2018-2022. Práce je rozdělena do tří části. V první teoretické části jsou vysvětleny metody a ukazatele, které jsou nutné pro vypracování finanční analýzy. Ve druhé analytické části jsou použity praktické metody a ukazatele pro vypracování finanční analýzy spolu se srovnáním výsledků konkurenčního podniku. V poslední návrhové části jsou představeny návrhy pro zlepšení celkové situace vybraného podniku.

The bachelor thesis deals with the evaluation of the financial situation of Podhoran Lukov, a.s. The financial analysis was carried out in the years 2018-2022. The thesis is divided into three parts. The first theoretical part explains the methods and indicators that are necessary for the development of the financial analysis. In the second analytical part, the methods and indicators are practically used to develop the financial analysis along with the comparison of the results of the competing company. In the last design part, suggestions for improving the overall situation of the selected enterprise are presented.
Evaluation of the Financial Situation of the Company and Proposals for its Improvement
Keywords: Finanční analýza; likvidita; rentabilita; poměrové ukazatele; rozvaha; výkaz zisku a ztrát; zadluženost; cash flow; Financial analysis; liquidity; profitability; ratios; balance sheet; profit and loss statement; debt; cash flow